Geochemical characterization of shore sediments and water of the Euphrates River between Keban and Karakaya Dams - Kalender, Leyla; Aytimur, Gamze (Gazi Univ, Fac Engineering Architecture, 2017)
The aim of this study is to determine the effects of the source rocks on distribution of major and trace element concentrations in the sediment and water samples from the Euphrates River, and Sr-Nd isotopic composition ratios in some of the sediments. The high concentration of Ag, As, Pb, Mn, Hg, Cu, Ba, Au, Mo, Hg and Zn in the river sediments may be considered to be sourced from wastes from the abandoned Keban mine deposit. In the study, the mean content of metals in the river water and river sediments were compared, and element concentrations in the river waters of some stable heavy metals (Ba, Cr, Hf and Zr) are lower than the other metal concentrations in studied river sediments and so they may be formed stable oxides and/or hydroxides, and thus are considered insoluble due to high density. The 143Nd/144Nd and 87Sr/86Sr isotopic compositions 0,7057-0,7048 and 0,512836-0,512654, respectively show that the source rocks for Nd and Sr are granodioritic and carbonate-rich meta-sedimentary rocks, respectively. 87Sr/86Sr ratio and Ca/Sr ratio indicate evaporite formations due to subtropical conditions. The obtained results show that hydromorphic distribution is a more effective factor on the studied river sediments than mechanical distribution.
Keban ve Karakaya Barajlari arasi Firat Nehri'nin kiyi sedimentleri ve su jeokimyasi özellikleri
Keywords: Euphrates River; sediment and water geochemistry; Nd-Sr isotopes